Healthy Community Movement (GERMAS) Education on Behavior and Knowledge of STIKes Bhakti Mulia Students - Maula, Liya Ni’matul; Setyadi, Ahmad Wasis; Yunita, Astri (Fakultas Ilmu Kesehatan, 2025)
Healthy Community Movement (GERMAS) is included in promotive and preventive efforts to the community which aims to reduce the burden Infection-related and chronic non-infectious diseases, reduce population productivity can be avoided, and health services can be reduced. The purpose of the study was to determine the effectiveness of GERMAS education on student behavior and knowledge. A quasi-experimental framework with a single group pre- and post-intervention evaluation was adopted in this study. The research sample was STIKes Bhakti Mulia students totaling 40 respondents. The experimental variable in this research is education, the dependent variable in the study is the behavior and knowledge of students. Measurement was carried out using a questionnaire that had been confirmed to be valid and reliable. Data analysis using Wilcoxon test. The research results confirmed that there was an effectiveness of GERMAS education on the behavior (p=0.000) and knowledge (p=0.000) of students. The conclusion of the study is that healthy behavior during adolescence can reduce the risk of chronic diseases in adulthood. Behavior and knowledge must be comprehensively owned by adolescents on several health issues, including nutrition, environmental health, infectious diseases, and health problems.